Understanding Transparency Failures: When Sunshine Causes Sunburns - Jean-Patrick Villeneuve; Marlen Heide; Giulia Mugellini (SAGE Open)
Recent years have seen an increase of critical perspectives on government transparency. Some consider its conceptualization too simplistic leading to over-enthusiastic promises. Other, more empirical studies show that transparency can create costs or adverse effects. This qualitative meta-analysis of scholarship reviews transparency research from 1996 onwards to map the pitfalls, shortcomings and negative dynamics of transparency policies. The analysis draws on policy studies, notably literature on policy failure. While systematizing the insights generated so far, the analysis also provides an overview of blind spots and shortcomings in transparency scholarship regarding the effects and outcomes of transparency policies.